The Efficacy of Acupuncture Therapy in the Management of Dyspnea and Other Symptoms Associated with Heart Failure: A Consolidated Review of Trial Data - Ganglani, Vishnu; Geng, Yong-Jian (Cells, tissues, organs, 2025)
Acupuncture has been used for pain management for thousands of years. However, it is largely unclear whether this therapeutic approach can effectively reduce heart failure-associated symptoms, including dyspnea. The hypothesis posited in this study was that acupuncture does indeed aid in the management of such symptoms and was motivated by the following statistics that establish a requisite need for efficient management of dyspnea to improve patient outcomes with heart failure. In 2020, an estimated 6.2 million adults in the USA had a heart failure diagnosis; in 2018, 379,800 death certificates reported heart failure; and the national cost of heart failure in 2012 was approximately USD 30.7 billion. The methodology employed to conduct this study involved review of trial data extracted from review of papers pertaining to acupuncture, symptoms of heart failure, and dyspnea, from academic and clinical data repositories subject to various inclusion and exclusion criteria. Of the initial set of 293 studies identified, the resulting inclusion set comprised 30 studies. The analysis conducted revealed that the highest frequency of combined acupuncture points prescribed for the foregoing search criteria were as follows: BL13, BL23, LU9, LU5, Dingchuan, LI4, PC6, and HT7. A meta-analysis of combined pooled p values for the studies revealed that acupuncture does aid in the management of symptoms of dyspnea and heart failure, subject to various limitations including but not limited to heterogeneity inherent between the studies in the inclusion set that were analyzed. Such limitations underscore the need to restrict generalizations from the conclusions of this study. The impact and novelty of this research study is its attempt to target the apparent paucity of literature that focuses on the management of dyspnea specifically in the context of heart failure with acupuncture and to bridge the gap of the application of acupuncture research on dyspnea to the cardiovascular context of heart failure. Notwithstanding the meta-analysis undertaken under this review study, further statistical analysis and a pilot study are warranted to consolidate or nullify the results of the research.